(untitled) (World Economics and Finance Bulletin, 2026)
The rapid growth of international tourist arrivals to Uzbekistan has created pressing demand for diversified and community-based tourism services, particularly in rural areas with high ecological and cultural value. Objective: This study examines how family-based entrepreneurial ventures can be established and scaled in eco-tourism destinations within the Samarkand region, with particular focus on the Urgut district villages of Omonqo’ton, Qoratepa, Yuqori Tersak, O’rta Tersak, and Tersak. Methods: A mixed-methods approach was employed, combining field assessment of existing tourism infrastructure, analysis of tourist route feasibility, and structured cost modelling for a four-day eco-tourism itinerary. Results: A 136-kilometre eco-tourism route encompassing five natural and cultural destinations was designed and costed at 789,570 Uzbek soums per person for a four-day trip. The largest cost components were destination entry fees (40.52%) and food services (30.39%). Discussion: The findings demonstrate that family enterprises in rural tourism can offer viable and competitive products when supported by organised route planning, safety information, and integrated service provision. Strengthening local data collection systems and expanding accommodation infrastructure remain critical priorities. Conclusion: Targeted policy support and structured capacity building for family-based tourism operators in the Samarkand region can meaningfully contribute to regional economic development and the sustainable growth of Uzbekistan’s tourism sector